Загальна характеристика авторських прав, які передаються в колективне управління - Ізбаш, Олеся Олегівна; Избаш, Олеся Олеговна; Izbash, O. (My University, 2012)
This article deals with the copyright, which are passed to the collective manage-ment. Collective management should be viewed as an activity of individual subjects to achieve the opportunities that appear in the content of property rights transferred by the author on a collective basis. Legislation in all counties tends to be given to the creators of the relevant material goods and Ukraine is no exception.
Ізбаш О. О. Загальна характеристика авторських прав, які передаються в колективне управління / О. О. Ізбаш // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2012. – Вип. 45. – С. 269-276.
Keywords: колективне управління; авторське право; авторское право; коллективное управление; Copyright; collective management